A Rasch Model Analysis on Junior High School Students’ Scientific Reasoning Ability - Wati, Mustika; Mahtari, Saiyidah; Hartini, Sri; Amelia, Heny (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Science education that emphasizes only the count is not relevant at the moment. Students must make scientific reasoning in answering the problem. This study aims to determine students’ scientific reasoning abilities in light matter. The method in this research was the descriptive method by using the survey technique. The instrument used is a description test consisting of 8 items of light matter. This test was conducted on 201 students from the eighth-grade junior high school in Banjarmasin selected at random. The RASCH model is used as a processing stage of data from raw data into logit numbers that provide information related to infit, outfit and unidimensionality using a winstep program to achieve this goal, this study investigated the quality of items from Item and person measure, Item Bias, item and person reliability, and variable map. The findings show that the scientific reasoning ability of the eighth-grade students can be at a low level. So researchers should strive to improve students’ scientific reasoning abilities in future research.